Succession of microbial functional communities in response to a pilot-scale ethanol-blended fuel release throughout the plume life cycle. (March 2015) - Ma, Jie; Deng, Ye; Yuan, Tong; Zhou, Jizhong; Alvarez, Pedro J.J.
Abstract: GeoChip, a comprehensive gene microarray, was used to examine changes in microbial functional gene structure throughout the 4-year life cycle of a pilot-scale ethanol blend plume, including 2-year continuous released followed by plume disappearance after source removal. Canonical correlation analysis (CCA) and Mantel tests showed that dissolved O2 (which was depleted within 5 days of initiating the release and rebounded 194 days after source removal) was the most influential environmental factor on community structure. Initially, the abundance of anaerobic BTEX degradation genes increased significantly while that of aerobic BTEX degradation genes decreased. Gene abundance for N fixation, nitrification, P utilization, sulfate reduction and S oxidation also increased, potentially changing associated biogeochemical cycle dynamics. After plume disappearance, most genes returned to pre-release abundance levels, but the final functional structure significantly differed from pre-release conditions. Overall, observed successions of functional structure reflected adaptive responses that were conducive to biodegradation of ethanol-blend releases. Highlights: GeoChip discerned microbial functional changes through an ethanol blend plume. The release increased gene abundance for anaerobic BTEX degradation. The release changed key biogeochemical (N, P, C, and S) cycling gene abundance. The functional structure did not recover 4 months after the plume attenuated. Dissolved O2 was the most influential factor shaping community structure. Abstract : Geochip analysis discerned adaptive shifts in microbial functional structure and controlling environmental factors throughout a 4-year life cycle of a pilot-scale ethanol blend plume.